أثر الطريقة الكلية في تعليم مهارة الدحرجة الأمامية على عارضة التوازن لدى طالبات كلية التربية الرياضية بجامعة تشرين - وطفة أُلفت; محمود بلال; يونس منارس (Latakia University Journal -Medical Sciences Series, 2019)
The research is based on the study of the man’s many arts, which show the strength, flexibility and flexibility of the man in all fields and fields, and the importance of gymnastics in this general sports activity, because it is characterized by the movement of beautiful men and women, and needs to perform agility and strength. It also deals with the improvement and development of motor skills, especially (the front roll on the balance model), the overall method is suitable for learning this skill, and thus gives the clear picture by making every skill and appropriate method of education used to develop and master. ينطوي البحث على دراسةِ ما يُقدمه الإنسان من فنون حركية عديدة يُظهر فيها ألواناً من قوته ورشاقته ومرونته في شتى الميادين والمجالات، ويُبين أهمية رياضة الجمباز في هذا النشاط الرياضي العام، ذلك لأنّها تتميز بالحركة اللّطيفة الجميلة عند الرجال والنساء، ويحتاج أداؤها إلى الرشاقة والقوة. كما يتطرق إلى تحسين وتطوير المهارات الحركية ولاسيما ( الدحرجة الأمامية على عارضة التوازن)، مما يتيح لنا التعرف على إن كانت الطريقة الكلية مناسبة لتعليم هذه المهارة، وبذلك يعطي الصورة الواضحة بجعل كل مهارة وما يناسبها من طريقة تعليم تستخدم لتطويرها واتقانها.